Pengaruh Motivasi dan Motivator Terhadap Kinerja Pada Karyawan PT. Pindo Deli Pulp and Paper Mills-2 - Muhammad Ichlasul Amal; Kusnadi Kusnadi; Asep Erik Nugraha (Jurnal Ilmiah Wahana Pendidikan, 2022)
This study is designed to analyze the relationship between variables so that this research belongs to the type of causal research. The variables used in this study are the independent variables, namely the material motivation and the material provider and the dependent variable, namely the employee performance variable. Primary data obtained by distributing questionnaires to 60 employees who attended the Culture House Training. The research was conducted using the Multiple Linear Regression Analysis Technique, F test, t test, and the coefficient of determination which were run by the SPSS application. Motivation material has no effect on employee performance, indicated by the t value of 1.429 is smaller than the t table value of 2.00247. Giver of motivation has an effect on employee performance, as indicated by the t value of 7.648 which is greater than the t value of 2.00247. Motivation material and material giver jointly affect employee performance, indicated by the value of the F count of 31.131 is smaller than the F table value of 3.16 with a significance level of 0.008 Based on the coefficient of determination test, it is known that the dependent variable influenced by the independent variable is 50.5%, while the rest is influenced by factors outside of this study. The results of this study indicate that the material of motivation and motivation has an influence on the performance of the employees of PT. Pindo Deli Pulp and Paper Mills-2. Based on the conditions that occur in the field, this research produces recommendations for future improvements related to motivation, motivation, types of delivery, and employee performance.